Modelo de exportación de pulpa de mango desde Colombia hacia Vancouver, Canadá (2020)
This document presents an approximation of an export process of mango pulp, in where we identify the actual situation of the fruit industry through the different global markets, making emphasis on the Colombian and Canadian market. For the development of this project, technical aspects of the treatment and transformation of the fruit into pulp were analyzed, identifying the processes and tools that are required to carry out the final product. Business strategies and a logistical profile are proposed to identify the correct way to enter the Canadian market, considering the regulations of both countries. Finally, a financial analysis is carried out, which allows identifying the costs associated with the project and thus predicting its financial viability, which will make it possible to carry out a process to export mango pulp to Vancouver, Canada.